(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This scientific article describes the results of the research work carried out to determine the reasons for the appearance of additional deformations (seismic prosadks) on moistened loam basess under the influence of dynamic (seismic) forces, the amount and their impact on buildings and structures. The article also provides an analysis of the results of the work of most specialist scientists on the study of additional deformations, i.e. seismic prosadks, that appear on lyosimal bases moistened by seismic forces at the time of an earthquake. At the same time, recommendations are also given to take into account the additional deformation that occurs under the influence of seismic forces in the design and construction of buildings and structures in earthquake districts in moistened sedimentary beds.